ANALISIS YURIDIS NORMATIF DAN HUKUM ISLAM TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 30-74/PUU-XII/2014 TENTANG BATAS USIA PERKAWINAN ANAK - Hasanain Haikal (UNISSULA, 2015)
Islam does not know the age limit, the groundwork in this case is quite strong because Rosul Saw himself married Siti Aisyah at the age of 6 years. So from the standpoint of Islamic law there is no gap. But Islam is not rigid if indeed conditions are in an emergency may be the law will change to follow the circumstances. The Constitutional Court rejected the petition ofthe judicial review, the Court considered the applicant’s argument unreasonable, and declared the petitioner’s refusal to the fullest. The judge considers that the age-specific requirement forwomen is tailored to many aspects, such as health, social, culture, and economics. In fact, there is no guarantee that raising the marriage age limit for women from 15 to 18 years will reduce the rate of divorce, tackling health problems, as well as other social issues. To prevent child marriage that caused many problems, according to the Court not only with the age limit alone. It is also possible that, based on various aspects of socioeconomic, cultural, and technological development, the age of 18 may be considered lower or higher.